De novo coronary artery disease in graves' disease. coincidence? - Dariush Shahsavari; Bryan Zoll (Greater Baltimore Medical Center, 2018)
Hyperthyroidism is associated with increased risk of cardiovascular conditions. We report a case of a 50-year-old woman with no prior cardiac history who presented to the emergency department with shortness of breath, chest pain, lower extremity swelling, and generalized fatigue. She was found to have Graves' Disease (GD) and extensive coronary artery disease (CAD), suggesting the possibility of increased risk of de novo CAD in patients with GD in the absence of other risk factors.